Efektivitas Penggunaan Media Pembelajaran Video Untuk Mencapai Tujuan Pembelajaran Ips Materi Letak Wilayah Indonesia Siswa Kelas VII SMP N 2 Banyudono - SULASTO, BIBIT (2016)
The background of this problem is the learning process of students in the class are still using conventional methods (lectures), so video media in learning is very necessary to create an atmosphere that is more interesting so that students in the class do not feel bored with the learning with video media. This research is quantitative research with the use of video media in learning. The purpose of this study was to determine the effectiveness of instructional video media compared to conventional methods in the matter lies the Indonesian territory of Class VII SMP N 2 Banyudono Boyolali. This research method using a type of experimental research using about Pre Test - Post Test. There are two classes in this research that experimental classes and classes using video media control using conventional methods (lectures). The population in this study is a class VII SMP Negeri 2 Banyudono Boyolali consisting of 8 classes with the number of 238 students. Total sample in this study is 68 students. Mechanical sampling using a convenience sampling (sampling potluck of the value of the highest average grade VII), of the study concluded that the control class has a value of post test by an average of 56%, when compared with the results of the post test experimental group increased after getting treatment is by using video media learning in classroom teaching and learning activities that have an average value of 74%, in this case the value of the average post test experimental class is higher because it has a difference of 18% with the average value of the control class. In conclusion instructional video media more effectively used in learning.